MEDICAL TABLETS PARACETAMOL AND MERTRONIDAZOLE AFFECTS WHEAT SEED GERMINATION AND SEEDLINGS GROWTH AS PLANT GROWTH REGULATORS - KHALAF, AHMED S.; OMER , FATHI A.; A. KHALIL, KHALIL (Journal of Duhok University, 2020)
Triazole derivatives are regularly used as systemic fungicides for seed dressing or as plant growth regulator, but it can cause numerous changes in plant morphological and physiological characteristics. An experiment included the local Iraqi bread wheat variety Tammuz-2 and the introduced Turkish ones Adana-99 were exposed to two concentrations (500 and 1000ppm) of the antibiotic medicinal tablets paracetamol and metronidazole, to illustrate the biological activity in terms of seeds germination and early seedlings growth traits; as they are structurally resemble the well-known azole fungicides and growth retardant derivatives. The results obviously revealed that these drugs exhibited growth regulatory activity in terms of their toxic effects in reducing of germination % from 84.5% to 69.75% for Tammuz-2 with paracetamol at 1000ppm, and from 84.50% to 76.00% with metronidazole at the same concentration. Similarly the germination% of Adana -99 was also dropped from 91.5 % to 77% and 82.5% for paracetamol and metronidazole at 1000ppm, respectively, this reduction in germination % was accompanied with increment in abnormal seedlings%. The deleterious impact on Adana-99 shoot length was exaggerated with metronidazole at 1000ppm which recorded (5.75 cm) in comparison to control (10.11cm). Concerning with the length of the longest rootlet, drastic reduction was noticed for both varieties with metronidazole at both concentrations 500 and 1000ppm, but the lowest was 1.47 cm at 1000ppm for metronidazole in comparison to the control 11.21cm for Tammuz-2 variety. The effect of drugs on number of rootlets resembled rootlets length as it was reduced by metronidazole, whereas the highest concentration 1000ppm only significantly reduced seedlings fresh weight.    Although there was discrepancy in seedlings dry weight as metronidazole particularly with high concentration caused drastic suppression in rootlets growth, but it resulted in higher dry weight, the interpretation for such ambiguity was that the seeds were not removed from the seedlings and it was contributed in whole seedlings weight and could be also due to the better food reserved in the germinated seeds. It was worth to declare that paracetamol treated seeds colored dark black, which was attributed to the tyrosinase enzyme activity present in seeds pericarp which oxidize phenol into quinines and subsequently converted to dark colored melanin by polymerization and interaction with protein. The results ascertained the side effect of these drugs as they possess regulatory behavior; therefore awareness required utilizing such pharmaceutical compounds to avoid unanticipated risk of soil contamination and agricultural ecosystems pollution